Recordkeeping Metadata Standardization for Electronic Health Records System Integration: a Preliminary Study - Intan Idayu Binti Shahrul Asari, Seri; Binti Hussin, Nurussobah; Zam Hariro Bin Samsudin, Ahmad; Nizam Bin Yunus, Mohd (International Journal of Engineering and Technology, 2018)
Electronic Health Records (EHRs) are beneficial in improving patient care, promoting safe practice, as well as enhancing patients and multiple providersâ€™ communication and risk error reduction. However, it seems that the adoption of EHR system is happening very slowly to become fully integrated in both primary care and within hospital settings. In Malaysia, the implemented system still has limited integration and interoperability for supporting clinical operations among other Ministry of Health Malaysia (MOHM) hospitals, health centres, and clinics. Therefore, the objective of this paper is to discuss about this scenario and strain the need for solution through the consideration towards metadata standard establishment in health records system integration. Method used in this study is literature review analysis and face-to-face interview. The paper begins with discussions from various literatures highlighting the need of metadata standard for recordkeeping system integration. Subsequently, the face-to-face interview is done to explore the real situation in Malaysia to encounter the scenario discuss in the literatures. The finding of this study reveals that there is significant need for further research on record keeping metadata standard development for realization of electronic health records system integration. This study is significant for records managers, information technology managers, system developers and record keeping audit.Â Â